2008
DOI: 10.1136/ard.2007.080002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of abatacept or infliximab vs placebo in ATTEST: a phase III, multi-centre, randomised, double-blind, placebo-controlled study in patients with rheumatoid arthritis and an inadequate response to methotrexate

Abstract: Objectives:This double-blind trial evaluated the efficacy and safety of abatacept or infliximab vs placebo. The primary objective of this study was to evaluate the mean change from baseline in Disease Activity Score (based on erythrocyte sedimentation rates; DAS28 (ESR)) for the abatacept vs placebo groups at day 197.Methods:Patients with rheumatoid arthritis (RA) and an inadequate response to methotrexate (MTX) were randomised 3:3:2 to abatacept (∼10 mg/kg every 4 weeks, n = 156), infliximab (3 mg/kg every 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
318
0
19

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(362 citation statements)
references
References 13 publications
23
318
0
19
Order By: Relevance
“…The AMPLE trial [2], a head to head comparison of ABA vs ADA demonstrated that overall AE and serious infections were significantly lower with ABA: SI rate of 3.8 compared to 5.8% in the ADA-treated group. Also, the ATTEST trial reported considerably lower rates of SI in patients treated with ABA (1.9%) vs IFX (8.5%) [30]. A metaanalysis by Salliot et al confirmed that ABA did not significantly increase the risk of SI in RA patients [31].…”
Section: Discussionmentioning
confidence: 98%
“…The AMPLE trial [2], a head to head comparison of ABA vs ADA demonstrated that overall AE and serious infections were significantly lower with ABA: SI rate of 3.8 compared to 5.8% in the ADA-treated group. Also, the ATTEST trial reported considerably lower rates of SI in patients treated with ABA (1.9%) vs IFX (8.5%) [30]. A metaanalysis by Salliot et al confirmed that ABA did not significantly increase the risk of SI in RA patients [31].…”
Section: Discussionmentioning
confidence: 98%
“…In clinical trials, abatacept was effective both as monotherapy (116) and when tested in combination with MTX (117). In a study in patients who had previously received anti-TNF drugs, abatacept could induce ACR criteria responses in a significant proportion of the patients involved in the trial (118).…”
Section: From Animal Models Toward the Clinicmentioning
confidence: 99%
“…As in AMPLE, these 3 abatacept studies included patients with an inadequate response to MTX who were biologics‐naive 5, 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%